Extracellular matrix abnormalities in the hippocampus of subjects with substance use disorder - Valeri, Jake; Stiplosek, Charlotte; O’Donovan, Sinead M.; Sinclair, David; Grant, Kathleen A.; Bollavarapu, Ratna; Platt, Donna M.; Stockmeier, Craig A.; Gisabella, Barbara; Pantazopoulos, Harry (Translational psychiatry, 2024)
Contextual triggers are significant factors contributing to relapse in substance use disorders (SUD). Emerging evidence points to a critical role of extracellular matrix (ECM) molecules as mediators of reward memories. Chondroitin sulfate proteoglycans (CSPGs) are a subset of ECM molecules that form perineuronal nets (PNN) around inhibitory neurons. PNNs restrict synaptic connections and help maintain synapses. Rodent models suggest that modulation of PNNs may strengthen contextual reward memories in SUD. However, there is currently a lack of information regarding PNNs in the hippocampus of people with SUD as well as how comorbidity with major depressive disorder (MDD) may affect PNNs. We used postmortem hippocampal tissues from cohorts of human and nonhuman primates with or without chronic alcohol use to test the hypothesis that PNNs are increased in subjects with SUD. We used histochemical labeling and quantitative microscopy to examine PNNs, and qRT-PCR to examine gene expression for ECM molecules, synaptic markers and related markers. We identified increased densities of PNNs and CSPG-labeled glial cells in SUD, coinciding with decreased expression of the ECM protease matrix metalloproteinase 9 ( Mmp9 ), and increased expression for the excitatory synaptic marker vesicle associated membrane protein 2 ( Vamp2 ). Similar increases in PNNs were observed in monkeys with chronic alcohol self-administration. Subjects with MDD displayed changes opposite to SUD, and subjects with SUD and comorbid MDD had minimal changes in any of the outcome measures examined. Our findings demonstrate that PNNs are increased in SUD, possibly contributing to stabilizing contextual reward memories as suggested by preclinical studies. Our results also point to a previously unsuspected role for CSPG expression in glial cells in SUD. Evidence for increased hippocampal PNNs in SUD suggests that targeting PNNs to weaken contextual reward memories is a promising therapeutic approach for SUD, however comorbidity with MDD is a significant consideration.